Machinability of Lead Free Copper Alloys - Madl, Jan; Koutny, Vaclav (Manufacturing Technology Journal, 2015)
Lead is traditionally used for completing free-machining materials. This paper deals with newly developed lead free copper alloys. Unfortunately, lead affects the haematological and nervous system. Therefore, materials containing lead represent one of the greatest environmental problems in world production. Research Material Institute in Panenske Brezany (CZ) developed new environmentally friendly cooper alloys. Machinability of these materials was tested at the Department of Machining, Process Planning and Metrology CTU in Prague. Some of the research results related to the machinability from the viewpoint of chip forms, surface roughness, cutting temperature, cutting time in drilling with constant feed force, and forces in cutting are presented.
Keywords: Machining; Cooper alloys; Lead free; Machinability